Criteria for selection of patients with lumbar intervertebral disc herniation complicated by spinal canal stenosis - T. А. Ksenzov; M. V. Khyzhniak; A. Ю. Ksenzov; V. О. Tyshchenko (Zaporožskij Medicinskij Žurnal)
Aim – to evaluate clinical and instrumental correlation (MRI data) in patients with lumbar intervertebral disc herniation complicated by spinal canal stenosis for optimizing the indications for differentiated surgical treatment.